2006
DOI: 10.1109/titb.2005.863877
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Experience for Chronic Care in COPD

Abstract: Abstract-Information and telecommunication technologies are called to play a major role in the changes that healthcare systems have to face to cope with chronic disease. This paper reports a telemedicine experience for the home care of chronic patients suffering from chronic obstructive pulmonary disease (COPD) and an integrated system designed to carry out this experience. To determine the impact on health, the chronic care telemedicine system was used during one year (2002) with 157 COPD patients in a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
138
1
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(151 citation statements)
references
References 14 publications
1
138
1
10
Order By: Relevance
“…Following review of titles and abstracts, full text of 48 reports were obtained for appraisal of relevance and quality. Finally, 10 trials were selected, [12][13][14][15][16][17][18][19][20][21] published in 12 reports [12][13][14][15][16][17][18][19][20][21][22][23] ( Figure 1) studying a total of 1004 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following review of titles and abstracts, full text of 48 reports were obtained for appraisal of relevance and quality. Finally, 10 trials were selected, [12][13][14][15][16][17][18][19][20][21] published in 12 reports [12][13][14][15][16][17][18][19][20][21][22][23] ( Figure 1) studying a total of 1004 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Description of studies A summary of the key characteristics of all 10 trials is given in Table 1. 12-21 Some of the studies 14,16,17,20 relied on videoconferencing or telephone communication to set up 'virtual consultations', sometimes in addition to face-to-face consultations. Key outcomes of emergency department visits and hospitalisations were studied across most studies, but only those four studies which investigated a period of 12 months contributed to meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The authors found that the integration of telemedicine with case management ''increased the number of patients who were not readmitted (51% intervention versus 33% control), is acceptable to professionals, and involves low installation and exploitation [utilization] costs.'' 127 The following two studies had samples fewer than our suggested standard of 150 cases. Nonetheless, they are included here because of some unique features.…”
Section: Health Outcomes and Costmentioning
confidence: 99%
“…'' 126 In 2006, an RCT (n = 157) conducted in Spain investigated the effects of an integrated telemedicine system on hospital re-admission rates and mortality. 127 The telemedicine service consisted of a call center, an application server, and an educational server, all connected to the patients' homes. The application server included three different applications: a Web-based Patient Management Module, a telemonitoring module, and a home visit server.…”
Section: Health Outcomes and Costmentioning
confidence: 99%
“…There are different technologies and timings for data collection, ranging from digital videophone systems, alone [25] or coupled with other systems [26] to weekly transmission of ventilator data through modems, weekly phone interviews by nurses coupled with oximetry download through modems [34,[46][47][48], daily oximetry readings [46][47][48], customised or commercial multifunctional devices [34,35,49]. For severe COPD patients with CRF tele-spirometry may help in the monitoring of lung function and complement the information in the VDIs [34].…”
Section: Equipment and Technology For Follow-upmentioning
confidence: 99%